A review article on importance of nidan panchak in ayurveda - Ankita Thakur; Akhilesh Kumar Srivastva; Rajesh Manglesh (International Journal of Pharmacy and Analytical Research, 2022)
There are many ways of diagnosis in Ayurveda but one of them is Nidan panchak . Nidan panchak is the one of the most important method to diagnose disease, its causes and prognosis. Nidan panchak is consist of five sub types which are Nidan (causes), Purvroop (symptoms), Roop(signs), Upshaya (examination methods) and Samprati (pathogensis). The diagnosis of disease in Ayurveda is done by Prakriti of the patient. Prakriti of the patient depends on the Dosha (Vata, Pitta, Kapha) Diagnosis of disease depends on Tridoshas which are Vata, Pitta, Kapha. By the imbalance of these Tridoshas disease occurs in the body. These imbalances in the body Doshas is due to lifestyle, diet and eating habits of the people. Diagnosis is the important component for the treatment of disease. In Ayurveda there are many techniques other than Nidan panchak which are used for the diagnosis of the disease they are Naadi pareeksha, Dashvidh pareeksha, Asthvidh pareeksha but in this article importance of Nidan panchak is explained.